PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH BELANJA HIBAH, DAN BELANJA BANTUAN SOSIAL, TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PEMERINTAH KABUPATEN BOGOR PROVINSI JAWA BARAT - Thantawi, Tubagus Rifqy; Khoiri, Abdul; Sakilah, Ilah; Imanudin, Teguh (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Regional development is an integral part of national development efforts which are emphasized through the principle of regional autonomy. According to the theory of government spending, when the government allocates a budget for development activities, it will contribute to an increase in aggregate spending and strengthen the country's level of economic activity. In other words, through government spending on regional development, it can encourage overall economic growth and increase economic activity in the country. The purpose of this study is to see that Grant Expenditure and Social Assistance Expenditure partially and simultaneously affect the Gross Regional Domestic Product, as well as to propose ideas for implementing good governance in the Bogor District Government so that Grant Expenditures and Social Assistance Expenditures can increase the impact that better towards growth and equity of the economy through the Gross Regional Domestic Product. The results of this study indicate that the X1 variable (Grant Expenditure) has a positive effect on Y (Gross Regional Domestic Product/GDP) of 0.266, the X2 variable (Social Assistance Expenditure) has a negative effect on Y (Gross Regional Domestic Product/GRDP) of -0.528 and also there is a significant influence between X1 (Grant Expenditures), and X2 (Social Assistance Expenditure), together on Y (Gross Regional Domestic Product/GRDP).